Distinct proteostasis circuits cooperate in nuclear and cytoplasmic protein quality control. (15th November 2018) - Samant, Rahul; Livingston, Christine; Sontag, Emily; Frydman, Judith
Abstract Protein misfolding is linked to a wide array of human disorders, including Alzheimer's disease, Parkinson's disease and type II diabetes1, 2 . Protective cellular protein quality control (PQC) mechanisms have evolved to selectively recognize misfolded proteins and limit their toxic effects3–9, thus contributing to the maintenance of the proteome (proteostasis). Here we examine how molecular chaperones and the ubiquitin–proteasome system cooperate to recognize and promote the clearance of soluble misfolded proteins. Using a panel of PQC substrates with distinct characteristics and localizations, we define distinct chaperone and ubiquitination circuitries that execute quality control in the cytoplasm and nucleus. In the cytoplasm, proteasomal degradation of misfolded proteins requires tagging with mixed lysine 48 (K48)- and lysine 11 (K11)-linked ubiquitin chains. A distinct combination of E3 ubiquitin ligases and specific chaperones is required to achieve each type of linkage-specific ubiquitination. In the nucleus, however, proteasomal degradation of misfolded proteins requires only K48-linked ubiquitin chains, and is thus independent of K11-specific ligases and chaperones. The distinct ubiquitin codes for nuclear and cytoplasmic PQC appear to be linked to the function of the ubiquilin protein Dsk2, which is specifically required to clear nuclear misfolded proteins. Our work defines the principles of cytoplasmic and nuclear PQC as distinct, involving combinatorial recognition by defined sets of cooperating chaperones and E3 ligases. A better understanding of how these organelle-specific PQC requirements implement proteome integrity has implications for our understanding of diseases linked to impaired protein clearance and proteostasis dysfunction. Ubiquitin chains linked to cytoplasmic misfolded proteins are different from those linked to nuclear misfolded proteins, each requiring a distinct combination of molecular chaperones and ubiquitination circuitries.